Marketing Plan Strategy in Achieving Marketing Goals at the Harmoni Physiotherapy Clinic - Shadiqy Artib; Rhian Indradewa; Rina Anindita; Ferryal Abadi (Journal of Social Research, 2026)
This research aims to formulate a strategic marketing plan for Harmoni Physiotherapy Clinic through an analysis of the marketing framework, STP (Segmenting, Targeting, Positioning) strategy, and the 7P marketing mix. This study uses a descriptive qualitative approach with analytical tools such as the Internal External (IE) Matrix, the Quantitative Strategic Planning Matrix (QSPM), and the Lean Canvas Model. The strategy focuses on market development and unique product services. The research findings indicate that Harmoni Physiotherapy Clinic’s marketing strategy positions itself in a narrow differentiation focus, with the advantages of robotic physiotherapy and hydrotherapy technology, which are not yet available from similar competitors in Bekasi City. The 7P marketing mix includes digital-based services for therapist registration and gender selection, competitive pricing, and integrated promotions through online (social media, SEO, webinars) and offline (hospital collaborations, community service) channels. Short- to long-term sales programs are managed through the “Walk In 12345” activity to ensure business sustainability, along with plans for expansion into the Greater Jakarta area outside Bekasi City in the fourth year. The study concludes that a structured marketing plan that leverages the advantages of robotic technology and a smart digital marketing strategy can be key for Harmoni Physiotherapy Clinic to win market competition in the physiotherapy healthcare sector.